Upaya Mengurangi Kecemasan Siswa dengan Penerapan Teknik Relaksasi pada Layanan Konseling Kelompok di SMP Negeri 19 Kota Jambi - Firda Mirantika; Rasimin Rasimin; Siti Amanah (Journal on Education, 2023)
This study is based on the existence of student anxiety phenomena that will happen to worsen and add specific problems in the world of education where there is a wide variety of anxiety experienced by students, anxiety experienced by students in school demanding properly penetrated by teacher guidance and counseling with the relaxation technique can reduce anxiety. The purpose of this study is to know the number of student anxiety condition of IX E grade in SMP Negeri 19 Jambi City before the group counseling service with relaxation techniques, knowing the steps of counseling group with relaxation techniques to reduce anxiety in the class IX E Student in SMP Negeri 19 Jambi City, knowing the number of student anxiety class IX E SMP Negeri 19 Jambi city is not a group counseling with relaxation techniques. This type of research is research service (PTL) subject of 8 students SMP country of 19 Jambi city with gender 5 women and 3 men. This study is a student who is experiencing anxiety caused by fear, anxious, thoughts too long so that it can disrupt the child's thinking skills will be afraid of not passing. This research is conducted with four cycles, each cycle consists of, planning, implementation, evaluation, reflection. To see the results of the cycle it performed with observation data collection, interview. The results of this study indicate that the anxiety of student SMP country of 19 Jambi City could be reduced by using relaxation techniques which obtained an increase of 85%. The first cycle with a percentage of 38%, obtained cycle two with a percentage of 44%, obtained a third cycle with 82% percentage, obtained a 4 cycle with a percentage of 85%. These results are expected to help teachers guidance and counseling in reducing student anxiety.